Diamond turning of soft semiconductors to obtain nanometric mirror surfaces - Fang, Fengzhou Z.; Venkatesh, Vasisht,C.; Zhang, G.X. (Springer Verlag, 2002)
Diamond cutting is a viable alternative to grinding and polishing in the fabrication of high-quality soft semiconductors. Investigation of indentation provides useful information for understanding the practical diamond cutting process of brittle materials. Cutting forces and temperatures were analysed using a Kistler dynamometer and an infrared technique. A zero rake angle cutting tool was found to be most efficient, partly because the effective rake is really a strong negative rake brought about by the peculiar configuration of very low feeds and depths of cut. This is explained by means of the comparison of the force distribution between conventional turning and ultraprecision machining. Atomic force microscopy and scanning electron microscopy were used to study the surfaces. Zinc sulfide gave subnanometric surfaces (0.88 m) and zinc selenide gave Ra values of 2.91 nm.